A Study of Listening Skills Through Movie - Sabrina Salsabila; Ade Aisyah Nazhwandini Panjaitan; Ikrar Sahputra (JELT : Journal of English Education, Teaching and Literature, 2024)
In language learning. Language skills consist of four aspects, namely: listening skill, speaking skill, reading skill, and writing skill. Hasanah, N., & Munawaroh, S. (2023). The four aspects of language skills above should be mastered if someone wants to master a language well. The purpose of this study is to describe the opinions of students in watching English Movie as a medium for learning English, especially listening. Through unstructured interviews, twenty-six participants shared their perspectives on watching movies as an alternative medium for learning English. The results showed that three students had the same opinion that watching English movies could improve their ability to learn English, especially listening. They further said that they gained some new vocabulary after watching the movie.